2019
DOI: 10.1038/s41598-019-46542-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of Andaman and Nicobar Islands in eddy formation along western boundary of the Bay of Bengal

Abstract: Eddies along western boundary of the Bay of Bengal (WBoB) play an important role in regulating regional climate and marine productivity of the north Indian Ocean. In this paper, role of Andaman and Nicobar islands (ANIs) in the formation of eddies along the WBoB is studied using an ocean general circulation model. Our analysis shows that, in the absence of ANIs, there is a significant reduction in the total number of mesoscale eddies in this region. The impact is particularly evident for the cyclonic eddies as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 34 publications
(50 reference statements)
2
10
0
Order By: Relevance
“…Interestingly, these coherent westward tilting structures, or wave packets, also appear to exhibit episodic eastward migration with systematic positive (orange) and negative ( Another common feature which we observe is the presence of shorter time scale (< 30 days) eddies or waves around 94 ∘ E-97.625 ∘ E, i.e. near the Irrawaddy river basin, through out the year (Mukherjee et al, 2019). We have also constructed Hovmöller plots of the zonal velocity with respect to latitude (not shown), these showed a fairly mixed behavior with sporadic instances of northward and southward tilts.…”
Section: Physical Space Characterizationsupporting
confidence: 55%
“…Interestingly, these coherent westward tilting structures, or wave packets, also appear to exhibit episodic eastward migration with systematic positive (orange) and negative ( Another common feature which we observe is the presence of shorter time scale (< 30 days) eddies or waves around 94 ∘ E-97.625 ∘ E, i.e. near the Irrawaddy river basin, through out the year (Mukherjee et al, 2019). We have also constructed Hovmöller plots of the zonal velocity with respect to latitude (not shown), these showed a fairly mixed behavior with sporadic instances of northward and southward tilts.…”
Section: Physical Space Characterizationsupporting
confidence: 55%
“…As internal tides propagate large distances through the varying oceanic conditions, they lose coherency with the barotropic tides and become incoherent (Nash, Shroyer, et al, ). Previous studies have shown strong activity of mesoscale eddies in the BoB (Chen et al, ; Mukherjee et al, ). Hence, the interaction of long‐range propagating internal tides with varying mesoscale fields could be important in the BoB.…”
Section: Discussionmentioning
confidence: 89%
“…The Kelvin waves then trigger southwestward-propagating Rossby waves, which result in large mesoscale structures in the bay (X. . The Andaman Islands and Nicobar Islands are also shown to be very important for the generation of these eddies; without these islands the number of eddies would have reduced to almost half in the western bay of Bengal (Mukherjee et al, 2019). These eddies provide much of the horizontal stretching and stirring of the tracers, including those relevant to the ecosystems.…”
Section: Implications For Biogeochemistry In the Baymentioning
confidence: 99%